PHYSICAL REHABILITATION OF LOW BACK PAIN BASED ON A CONCEPTUAL SYSTEM APPROACHES - Olena LAZARIEVA; Mirosława CIEŚLICKA; Błażej STANKIEWICZ; Radosław MUSZKIETA; Krzysztof Prusik (H.S. Skovoroda Kharkov National Pedagogical University, 2014)
In Europe, back pain is a common disease, this is according to European statistics. In accordance with the new case, the pain each year occurs in 5% of the population. The aim of this work is to develop a conceptual approaches to the physical rehabilitation process at the surgical treatment of patients with back pain. Materials and methods . There was researched an experience of the domestic and foreign researches in physical rehabilitation area. Methods of the research were the analysis of the references and theoretical research methods (as an analysis, interpretation and synthesis of scientific and educational literature on the study problem. Abstraction (or idealization and schematization) is the allocation of the essential foundations. Also we used experimenting with schemes (as a development of their content, sophistication and usability testing) at development of concepts, practical models and physical rehabilitation programs. Results. The physical rehabilitation concept at the surgical treatment of patients with back pain was developed, given by the modern science in the diagnostics field, performing difficult complex spinal surgery with the using of new tools and the knowledge from the physical rehabilitation improvement. Conclusion. The using of a systematic methodology for physical rehabilitation in the surgical treatment of patients with vertebral pathology, helps to optimize research, diagnostic, therapeutic, rehabilitative and preventive measures, providing them with the required comprehensiveness, consistency, orderliness.